Measuring Subjective Movie Evaluation Criteria: Conceptual Foundation, Construction, and Validation of the SMEC Scales. Issue 1 (2nd January 2017) - Schneider, Frank M.
ABSTRACT: Audiences' movie evaluations have often been explored as effects of experiencing movies. However, little attention has been paid to the criteria viewers use when they evaluate a movie or its specific features. Adding to this, the present research introduces the idea of subjective movie evaluation criteria (SMEC), conceptualizes SMEC as the mental representation of important attitudes toward specific film features, and describes the scale construction for their measurement and its validation process. Findings from pilot work and 2 studies including over 1, 500 participants provide first evidence that 8 dimensions—Story Verisimilitude, Story Innovation, Cinematography, Special Effects, Recommendation, Innocuousness, Light-heartedness, and Cognitive Stimulation—are largely determined by stable individual differences, substantially but differentially related to film-specific constructs and personality traits, and that the SMEC scales are reliable and valid instruments for measuring subjective movie evaluation criteria.